PERANCANGAN BUKU EDUKASI BAHAYA MAKAN MAKANAN JUNK FOOD UNTUK ANAK ANAK - Rahmat Ferdian; hendra afriwan; syafwan syafwan (Universitas Negeri Padang, 2020)
The purpose of designing an illustrated book on the dangers of junk food for children as an educational and interactive media in the delivery of the dangers of junk food meals so that children reduce to avoid consuming junk food foods and prefer to eat healthy foods, vegetables and fruit that is useful for health and for the development and growth of children. This illustrated book was chosen as one of the educational media for children because it presents stories and illustrations of characters that make children enthusiastic to read it, so learning is more fun.The data analysis method in the 5W + 1H technique is (what, where, who, why and how) to find a solution to the problem at hand. Data collection was carried out using interview and documentation methods. Illustration, typography, and layout are designed using visual communication design theory, child psychology, media, books, illustrations, colors, layouts and typography. In addition to designing illustration books as the main media, this design has supporting media such as posters, x-banners, stickers, coloring books, notebooks, tote bags, and food supply boxes.Keywords: Book, Illustration Education, Junk Food, Children